Analisis Sistem Dropship Dalam Jual Beli Online Perspektif Ulama Klasik Dan Kontemporer - Midisen, Kisanda; Ahmad, Ali Nur; Marshella, Marshella (ITB AAS INDONESIA Surakarta, 2024)
The aim of this research is to find out the contracts applied to online buying and selling using the dropship system and the laws according to classical scholars and contemporary scholars. This qualitative research uses a descriptive analysis method with a process of collecting data from various sources; observations, interviews, and literature studies in journals, books, and articles relevant to the research topic. The approach used in this research is a phenomonological approach. Based on research findings, it can be said that the dropship system in online buying and selling is not prohibited in Islam and can be used with various contracts, including salam sale and purchase contracts, wakalah bil ujroh contracts, and samsarah contracts. The dropship method fulfills the prerequisites and principles of trade legitimacy in Islam. The permissibility of this dropship system refers to the general rule of muamalah fiqh which says